Contaminação e diagnóstico experimental de morangos (Fragaria vesca) por Giardia duodenalis - Barreto, Bárbara Melina Viol (2013)
The consumption of fresh fruits is a means of transmission of various organisms that cause diseases both infectious as parasitic, and contamination occurs from cultivation to manipulation. The strawberry production in Brazil has grown in recent years. Species of Giardia sp intestinal parasites which are disposed in the environment with the feces carrier (cysts) providing disperse hosts by ingesting contaminated water, vegetable or fruit usually eaten raw. There are limited data in the literature on the transmission of parasites carried by fruit and vegetables. This is due to methodological difficulties in diagnosing scarce evolutionary forms of protozoa, unlike bacteria. The objective of this study was to analyze the process more suitable for the diagnosis of Giardia duodenalis in strawberries. Each sample was contaminated with concentrations ranging from 10, 100 and 1000 cysts of Giardia duodenalis, founded the Laboratory of Environmental Parasitology, State University of Maringá. Each experiment was done in triplicate and the mean of the number of cysts evidenced. For both forms of contamination, immersion and dripping, the fruits were left at room temperature for 15 minutes. Each sample was placed on strawberry glass beaker, sterile, then infected with 400 mL of water Milique containing different concentrations of cysts. Then washed in the same solution, and the liquid is divided into three equal parts. A check for the presence of cysts by Giardia duodenales technique Faust et al, one for spontaneous sedimentation technique (Hoffman, Pons & Janer) and the third by direct immunofluorescence (Merifluor). Immersion of strawberries in Giardia causes greater contamination among fruits compared to drip on them. The results showed that the direct immunofluorescence technique detected higher amounts of contaminated samples as well as higher number of cysts. Even with this technique, visualization of the parasite could be observed in samples containing either 100 cysts / 100g sample of 50g of strawberry and for the same fruit. Lesser extent, the spontaneous sedimentation technique allowed some findings of cysts and technique of Faust et al, except for one sample, showed no contamination of the strawberries. This is the first work in the literature that seeks to establish a protocol for contamination of samples and experimental diagnostics strawberry (Fragaria vesca). The analysis in triplicate of strawberries, with samples of 100 or 50g, using the technique of direct 10 immunofluorescence (Merifluor) can be a useful tool in the study of Giardia, the public health agencies responsible for sanitary inspection.